COMPARATIVE ANALYSIS OF THE CASE SYSTEMS IN UZBEK AND GERMAN LANGUAGES - Khatamkulova Sh (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Introduction In the language system, grammatical categories are among the main tools that regulate speech. One of the most important of these categories is the case category, which determines the grammatical functions of nouns in a sentence and their relationships with other words. Through cases, syntactic-semantic relations such as subject, object, possession, direction, and others are expressed. Therefore, the case system plays an important role in understanding the grammatical structure of any language. Uzbek and German belong to different typological groups: Uzbek is an agglutinative language, while German belongs to the inflectional (fusional) language type. This difference is clearly reflected in the expression of case. In Uzbek, cases are mainly formed by attaching suffixes to nouns, whereas in German they are expressed through changes in articles, nouns, and pronouns. Despite these differences, in both language systems the primary function of case is to clarify grammatical relations within the sentence structure. In modern comparative linguistics, comparing structurally different languages makes it possible to identify their common and distinctive features. A comparative study of the case systems in Uzbek and German is particularly important both theoretically and practically for Uzbek-speaking learners of German. Therefore, this research aims to analyze the grammatical and functional aspects of the case category based on the two languages. The case category is not only morphological and syntactic but also a semantically and typologically significant part of the language system. Modern comparative linguistic studies show that although cases are expressed differently across languages, their primary function is to clarify the relationships between subject and object and to make sentence meaning clear. In Uzbek, cases are formed through an agglutinative mechanism and, together with relatively free word order, ensure semantic clarity. In German, cases interact with articles and noun forms and are connected with gender and number, which increases morphological complexity. These aspects provide an important basis for comparative and typological analysis and help develop effective approaches for Uzbek speakers learning German.